ASTRO Guidelines on Radiation Therapy in Endometrial and Lung Cancers - Nichols, Emma Hitt (MD Conference Express, 2014)
This article reviews the American Society for Radiation Oncology (ASTRO) evidence-based guidelines on the role of postoperative radiation therapy in patients with endometrial cancer. Also discussed are recommendations to serve as guidelines for definitive and adjuvant radiotherapy treatment in patients with locally advanced non-small cell lung cancer.